The Role of Chronic Inflammation in Stunting-Associated Cognitive Impairment in Hanoi, Vietnam - Simone Thanh Nguyen; Marcelle Thrinh (Scientific Journal of Pediatrics, 2024)
Introduction: Stunting, a manifestation of chronic undernutrition, affects millions of children globally and is associated with impaired cognitive development. Chronic inflammation, often triggered by recurrent infections and poor nutritional status, is hypothesized to play a crucial role in this association. This study aimed to investigate the relationship between chronic inflammation, stunting, and cognitive impairment in children under five years old in Hanoi, Vietnam. Methods: A cross-sectional study was conducted involving 300 children aged 6-59 months from various districts in Hanoi. Anthropometric measurements were taken to assess stunting (height-for-age z-score < -2 SD). Cognitive function was evaluated using the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III). Blood samples were analyzed for inflammatory markers, including C-reactive protein (CRP), alpha-1-acid glycoprotein (AGP), and interleukin-6 (IL-6). Socioeconomic status and dietary intake were assessed using questionnaires and 24-hour dietary recalls. Results: The prevalence of stunting was 23.3% in the study population. Stunted children exhibited significantly lower cognitive scores compared to non-stunted children (p<0.001). Elevated levels of CRP and AGP were observed in stunted children, indicating the presence of chronic inflammation. After adjusting for potential confounders, chronic inflammation was independently associated with cognitive impairment in stunted children. Specifically, elevated CRP and AGP levels were associated with lower scores in cognitive domains such as language, motor skills, and cognitive development. Conclusion: This study provides evidence for the role of chronic inflammation in mediating the link between stunting and cognitive impairment in children from Hanoi, Vietnam. Addressing chronic inflammation through improved nutrition, infection control, and targeted interventions may be crucial for mitigating the adverse cognitive effects of stunting.